THE PROCEDURE FOR THE PARTICIPATION OF SMALL BUSINESS ENTITIES-AGRICULTURAL PRODUCERS IN THE PUBLIC PROCUREMENT PROCESS - Svetlana N. Kovalenko; Natalia A. Prodanova; Nana D. Georgadze; Anton A. Sergeenkov (Siberian Journal of Life Sciences and Agriculture, 2023)
Background. Currently, agro-industrial holdings occupy a dominant position in Russia, which creates certain imbalances both in the agricultural and processing industries of the agro-industrial sector of the economy. In this connection, it is necessary to create conditions for the full functioning of SMP-agricultural producers. For this purpose, cooperation, conclusion of contracts or participation in state and municipal procurement can be used.